Complexity and complex thought: A brief introduction and current challenges - Mariotti, Humberto (2007)
Complexity is linked to multiple, interlacing, webbing and continuing interactions between an infinite number of systems within our world, human societies, persons and all living things. Complexity cannot be reduced to over-simplified explanations, rigid rules, simplifying formulas or closed constructs. An open, comprehensive and flexible way of thinking is needed - complexity thinking. The linear mental model and «or/or» disjunctive logic, that almost exclude complementarities and diversity, can, nevertheless, be combined with an integrative mental model as well as an «and» inclusive logic. Both are necessary and useful models, taking into account the nature and characteristics of the problems and circumstances to be approached. In the case of medicine and health care, the issues of perception, objectivity, subjectivity, causality models, explanations of effects, understanding of human behaviour, the doctor-patient relationship and many others may be explored using new concepts and some new practical instruments from complex adaptive systems theory. They also may help us to change our ways of looking at our world, of thinking about it and, consequently, of acting upon it.